Observations on gathering and departure of Pink-footed Geese at Asgard in central Iceland - Gillmor, Robert; Blurton Jones, N G (Wildfowl, 1954)
We spent six weeks in western central Iceland during the late summer of 1954--from 20 August to 14 September-- at Asgaro was a gathering place for about 350 Pinkfeet, which joined together into flocks. The gathering movements are probably social rather than migratory. Breeders and their goslings seemed to arrive from outlying areas such as the colony at Kisubotnar, and after flocking left in the direction of the Djrsrver and Djrs. The gathering probably retraces a dispersal in spring as the snow melts, first on lower ground, later on higher ground. On 2 and 3 September the Asgaro area was covered in snow. The geese left, apparently for the snow-free Djrs valley. Passage birds thought to be from Greenland then gathered but on 12 September snow started again. On the 13th the Asgaro flocks left in the blizzard and geese passed through all day. The first arrivals in Britain were on the 13th and 14th. Information on other years is summarised and compared with 1954. Departure seems to be solely a result of snow in the interior. At first the geese fly away downwind. The direction of migration is influenced by terrain and then by south-east drifts in the almost invariable conditions following any depression over Iceland which causes snow high up in the interior in September. It is thought that the geese reach the north coast of Scotland mainly as a result of these conditions. The coincidental but inevitable nature of this weather migration of Pinkfeet is contrasted with that of passerine and other birds leaving Iceland. Brood counts were made between 20 August and 1 September. There was no indication of gosling losses during this period. The mean brood-size was 3.1, substantially smaller than the mean of broods seen in Djrsrver in July (in 1951 and 1953). Two British-ringed and at least ten Djrsrver-ringed Pinkfeet were seen.